2015
DOI: 10.3174/ajnr.a4596
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Level-Dependence of Fatty Infiltration in Lumbar Paravertebral Muscles of Healthy Volunteers

Abstract: BACKGROUND AND PURPOSE:Normative age-related decline in paravertebral muscle quality is important for reference to disease and risk identification in patients. We aimed to establish age-and vertebral level-dependence of paravertebral (multifidus and erector spinae) muscle volume and fat content in healthy adult volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

37
167
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(220 citation statements)
references
References 40 publications
37
167
4
1
Order By: Relevance
“…Although none of the effect moderators affected our main outcome, our study agreed with the existing evidence about the correlation between fat infiltration in LMM and age [35, 36], gender [17, 36], duration of pain [8] and BMI [15, 19]. …”
Section: Discussionsupporting
confidence: 90%
“…Although none of the effect moderators affected our main outcome, our study agreed with the existing evidence about the correlation between fat infiltration in LMM and age [35, 36], gender [17, 36], duration of pain [8] and BMI [15, 19]. …”
Section: Discussionsupporting
confidence: 90%
“…It is acknowledged that acquiring such data is time-consuming, even using semi-automated or automated programmes. By way of potential compromise toward a time-efficient capture of lumbar paravertebral MFI on the basis of volume, Crawford et al [5] have shown that the fat content at L4 best represents that of the entire lumbar region in healthy participants. Measuring multiple slices at this level alone may present an effective option in busy clinical radiology environments, although further data are required to support the validity and reliability of the technique.…”
Section: Discussionmentioning
confidence: 99%
“…cross sectional area and/or volume alone) in the assessment of muscle degeneration [1417]. However, inconsistent associations are also reported [18] and confounded by normative age-related changes [5, 7, 19], degenerative features of the vertebrae or discs [9, 19, 20], and spinal curvature [21, 22]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 With respect to physical function, evidence suggests that muscle quality, i.e. intramuscular fat, may be more important than size.…”
mentioning
confidence: 99%